Streptococcus pneumoniae DNA Initiates Type I Interferon Signaling in the Respiratory Tract - Dane Parker (American Society for Microbiology, 2011)
ABSTRACT The mucosal epithelium is the initial target for respiratory pathogens of all types. While type I interferon (IFN) signaling is traditionally associated with antiviral immunity, we demonstrate that the extracellular bacterial pathogen Streptococcus pneumoniae activates the type I IFN cascade in airway epithelial and dendritic cells. This response is dependent upon the pore-forming toxin pneumolysin. Pneumococcal DNA activates IFN-β expression through a DAI/STING/TBK1/IRF3 cascade. Tlr4−/−, Myd88−/−, Trif−/−, and Nod2−/− mutant mice had no impairment of type I IFN signaling. Induction of type I IFN signaling contributes to the eradication of pneumococcal carriage, as IFN-α/β receptor null mice had significantly increased nasal colonization with S. pneumoniae compared with that of wild-type mice. These studies suggest that the type I IFN cascade is a central component of the mucosal response to airway bacterial pathogens and is responsive to bacterial pathogen-associated molecular patterns that are capable of accessing intracellular receptors. IMPORTANCE The bacterium Streptococcus pneumoniae is a leading cause of bacterial pneumonia, leading to upwards of one million deaths a year worldwide and significant economic burden. Although it is known that antibody is critical for efficient phagocytosis, it is not known how this pathogen is sensed by the mucosal epithelium. We demonstrate that this extracellular pathogen activates mucosal signaling typically activated by viral pathogens via the pneumolysin pore to activate intracellular receptors and the type I interferon (IFN) cascade. Mice lacking the receptor to type I IFNs have a reduced ability to clear S. pneumoniae, suggesting that the type I IFN cascade is central to the mucosal clearance of this important pathogen.